LESSON LEARN FROM THE INDIGINEOUS COMMUNITY TO MANAGE ENVIRONMENT AND DEVELOPING THE TOURISM OBJECT IN THE TAJI VILLAGES MALANG REGENCY, INDONESIA - Heni MASRUROH; SUMARMI; Fatiya ROSYIDA (Geo Journal of Tourism and Geosites, 2022)
This research was conducted in Taji Village which is a village located in the Bromo Tengger Semeru (BTS) area. The purpose of this study is to explore the strategy of the local community of Taji Village in preserving the environment to support the development of the Tourism Village. The method was conducted through physical surveyand socio-economic surveys. This research started from environmental physical research in the form of landslides with a geomorphological approach. Data collection on conservation efforts and socio-economic conditions was carried out through deep interviews, purposive questionnaires and deep interviews and also observations at tourist attractions in Taji Village. Based on the results of the study, it shows that the people of Taji Village are very aware that their area is an area that is prone to landslides. The local community of Taji Village has local wisdom as a conservation effort in the form of planting multi-strata plants on each part of the slopes in Taji Village with woody plants and horticultural crops. Conservation efforts with vegetative techniques through multi-strata plants, which are part of local wisdom actually make Taji Village a village that has a tourist destination i.e Arabica coffee cultivation and supporting tourism development such some of waterfall in Taji Village. Local wisdom carried out by the local community of Taji Village is also a community survival strategy because most of the life of the Taji Village community depends on the results of agriculture with weekly, monthly and annual harvest times.